Two-step sintering strategy to prepare dense Li-Garnet electrolyte ceramics with high Li+ conductivity. Issue 5 (1st April 2018) - Huang, Xiao; Xiu, Tongping; Badding, Michael E.; Wen, Zhaoyin
Abstract: One of the typical solid-state sintering strategies for Li-Garnet solid electrolytes is firing the green ceramics at one specific sintering temperature for a long period of time. When the sintering temperature is too low, the contact between grains is not good, resulting in relatively low relative density and poor conductivity. When the temperature is too high, the abnormal grain growth (AGG) phenomenon of Li-Garnet may occur, resulting in low strength. In this work, a novel two-step sintering strategy is applied to prepare Li-Garnet ceramics. This method involves one short-time high-temperature sintering process and one long-time low-temperature annealing process. Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO)-MgO composite electrolyte ceramics sintered by this method can have the properties of high conductivity (5.0 × 10 −4  S cm −1 ) at room temperature (RT), high relative density (98%), dense cross-sectional microstructure and high fracture strength (160 MPa). Besides, pure LLZTO ceramics sintered via two-step method shows dense microstructure, high conductivity (7.3 × 10 −4  S cm −1 ) at room temperature and high relative density (97%).